O hábito audiovisual: o abandono da possibilidade de ação imediata como modo de conduta - Bohn, Marcos Beck (2020)
This work is dedicated to what it intends to conceptualize as an audiovisual habit. For such a habit to be constituted, in the way as considered here, the first necessary condition is the existence of a relation of relative immobility between individual and audiovisual apparatus. Following Peirce's pragmatism, which considers the conception of an object as the totality of effects of the conception on the conduct of the conceptualized object, the personaudiovisual relation is defined precisely from the phenomenological verification that such non-movement relation between person and apparatus has occurred as an observable manifestation. In a second stage, considerations about the possible generality of such a relation are elaborated, which would make it no longer a multiple topical instance, but an insufficient predicate for the identification of individuals who share it. As a third point based on the Peircean approach, it is intended to understand the formation of an – thus considered and apparently established – audiovisual habit. Then, reflections on the perceptual process when facing audiovisual devices are developed. For that, the Bergsonian understanding of perception is followed, which sees it as a measure of the possible action on things and of things on the entity that perceives. In such reciprocity, conscious living beings become centers of indeterminacy, because, according to Bergson, they acquire decision-making capacity over eventual actions to be undertaken in the material world – a process in which the affections, a type of body effort on itself, would be a fundamental component. However, in face of the audiovisual, the perceived images no longer present the materiality that is inherent to them in the material world. Since there seems to be no longer any possibility of materially immediate action in such a situation, the reflection conjectures whether there would be any perceptual contradiction for the being who is placed in it. Finally, once the research is mostly dedicated to the human relation with audiovisual images, the Deleuzian approach to what would be movement-images is, to some extent, considered: notably, in the aspect that is most relevant here, the absence of an immediate materiality in images presented by audiovisual devices. Although Deleuze attributes the discovery of a movement-image to Bergson, claiming that there is in his thinking the notion of the material universe as a metacinema, a comparative reading between Bergson’s original passages and the interpretation that Deleuze gives them suggests that there is some level of extrapolation in Deleuzian application of Bergsonian thought. Nevertheless, the concept of metacinema remains afloat: no longer as encompassing the totality of the material universe, but as a world in which the abandonment of the possibility of immediate action seems to be a mode of conduct. A world of audiovisual habit, a world as metacinema